Work related to reproductive health risk analysis for female healthcare workers - Herawati, Dian; Rahmawati, Shofiyah Arviana (Poltekkes Kemenkes Yogyakarta, 2024)
Female workers have a risk of being exposed to various hazards in the work environment which can cause health problems including of reproductive health. However, evidence linking workplace hazards—such as job type, work shift, and exposure to chemical, biological, or physical agents—with menstrual and pregnancy disorders remains limited. This study aims to analyze work related to reproductive health risk of female healthcare workers at the hospital. A cross-sectional quantitative study using path analysis was conducted at Gadjah Mada University Academic Hospital, Indonesia, from April to November 2022. A total of 71 female healthcare workers (doctors, nurses, midwives, pharmacists, radiologists, and allied professionals) were recruited using stratified random sampling. Data were collected through structured questionnaires, interviews, and field observations, covering sociodemographic characteristics, work-related exposures, menstrual disorders, and pregnancy outcomes. Path analysis with regression modeling was performed to assess direct and indirect effects, and model fit was evaluated using standard indices. The majority of respondents were aged 20–35 years (72%), nulliparous (61%), and non-nurse medical staff (56%). Menstrual disorders were reported by 46% of participants, while 39% experienced pregnancy-related complications (e.g., abortion, preeclampsia, preterm birth). Exposure to chemical hazards was reported by 65%, biological hazards by 68%, and radiation by 38%. Path analysis showed that agent exposure (direct effect = 0.392, p<0.05) and work shift (direct effect = 0.223, p<0.05) significantly increased the risk of pregnancy disorders, while type of job influenced outcomes only indirectly (direct effect = 0.105; indirect effect = 0.210). The model explained 71.9% of the variance in pregnancy disorders (R² = 0.719).Occupational hazards, particularly agent exposure and shift work, are significant predictors of reproductive health problems among female healthcare workers. These findings highlight the need for institutional policies on safer shift scheduling, exposure monitoring, and reproductive health protection in hospital settings. Strengthening occupational health regulations is essential to safeguard maternal and fetal outcomes in the healthcare workforce.